A recessive mutation in rice conferring non-race-specific resistance to bacterial blight and blast - Madamba, Ma. Reina Suzette; Sugiyama, Nobuko; Bordeos, Alicia; Mauleon, Ramil; Satoh, Kouji; Baraoidan, Marietta; Kikuchi, Shoshi; Shimamoto, Ko; Leung, Hei (Springer, 2009)
To understand the basis of broad-spectrum disease resistance in rice, we isolated a gamma-ray-induced IR64 mutant G978 that showed enhanced resistance to blast and bacterial blight. The resistance is quantitative and non-race specific against the bacterial and fungal pathogens. The mutation is inherited as a single recessive gene, designated as Bsdr1 and causes shorter stature relative to the wild type; however, it does not show lesion mimics phenotype under the conditions tested. The mutation was mapped as a quantitative trait locus to a 3.8-Mb region on chromosome 12. By comparing the gene expression profiles of the mutant and wild type, we identified a candidate gene encoding a U-box domain-containing protein. The disrupted gene showed a loss of expression in the mutant and co-segregated with mutant phenotype. The mutant provides a useful tool for investigating the important genes responsible for non-race specific resistance to two distinct diseases.